Novel Heterozygous Mutations in JAG1 and NOTCH2 Genes in a Neonatal Patient with Alagille Syndrome - Alisa Brennan; Anil Kesavan (Case Reports in Pediatrics)
Alagille Syndrome (ALGS) is a rare autosomal dominant disorder that affects multiple organ systems. Cholestasis as a result of a paucity of intrahepatic bile ducts and congenital heart defects are the two most common features of ALGS. We describe a case of ALGS with novel mutations of JAG1 and NOTCH2 genes in a newborn girl with complex congenital heart disease, bilateral dysplastic kidneys, and malrotation with volvulus.